Craft souvenirs: perceived authenticity and tourists purchase behaviour / Farah Izzati Basri - Basri, Farah Izzati (2013)
The craft industry contributes in giving such a huge benefit towards Malaysia’s economic and increasing in sales of the local Small Medium Enterprise (SME). Therefore it is really important to sustain the originality and quality of the local craft souvenirs that represent our country in order to gain interests from the tourists. The worrying parts are the growing demand for craft souvenirs and other merchandise has resulted in imitation of craft product elsewhere, or even imported from other countries. This has caused tourists misleading the product originality as they may think that it is locally made. Moreover, these products have been sold together with the local products in the market. This study empirically investigates on how tourists determine the authenticity of the local craft souvenirs and how tourists perceived authenticity of craft souvenirs has influenced their purchase behavior. By using a self-administered questionnaire, findings revealed that majority of the respondents agreed on the uniqueness and originality, material, cultural and historic integrity as well as the price attributes portray the authenticity of the craft souvenirs. The result indicates that most of the respondents agreed on the price and cultural and historic integrity attributes were the most influenced attributes to their buying behavior. The result also revealed that majority of the respondents also wants to repurchase the local craft souvenirs on their next visit. Therefore, craft’s local SME should produce more authentic product in order to cater the demand from the tourists.